INTERACTION BETWEEN ECONOMY AND PEDAGOGY: EFFECTIVE MANAGEMENT OF ECONOMIC RESOURCES IN EDUCATION (International journal of artificial intelligence, 2025)
This article analyzes the interactions between economics and pedagogy, and the importance of effective management of economic resources in the field of education. The effectiveness of the education system depends not only on its quality, but also on the financial and material resources allocated to it. The article examines the impact of economic resource management on the educational process and how to maintain a balance between pedagogical goals and economic interests. It also shows how the correct distribution of economic resources in the education system and their effective use can influence the improvement of the quality of education. The article highlights the prospects and current problems of effective management of economic resources in the field of education in the context of Uzbekistan.